2001
DOI: 10.1128/aac.45.8.2316-2323.2001
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Infusion of Cereport Increases Uptake and Efficacy of Acyclovir in Herpes Simplex Virus-Infected Rat Brains

Abstract: The outcome of herpes simplex virus (HSV) infections manifesting as encephalitis in healthy or immunocompromised individuals is generally very poor with mortality rates of about 8 to 28% with treatment. The long-term prognosis of survivors is often problematic, posing the need for alternative treatments that may decrease the mortality and morbidity associated with herpes encephalitis. This study addresses one such approach that includes a temporary permeabilization of the blood-brain barrier during treatment w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…Our ED 50 of ϳ100 mg/kg t.i.d. for valacyclovir is in good accordance with the findings presented in a recent report in which only acyclovir doses greater than 100 mg/kg were able to reduce mortality in a rat model of HSV infection (2).…”
Section: Discussionsupporting
confidence: 81%
“…Our ED 50 of ϳ100 mg/kg t.i.d. for valacyclovir is in good accordance with the findings presented in a recent report in which only acyclovir doses greater than 100 mg/kg were able to reduce mortality in a rat model of HSV infection (2).…”
Section: Discussionsupporting
confidence: 81%
“…It has been suggested that investigating means to increase permeability of the BBB to enhance entry of antiviral agents into the CNS may provide a therapeutic strategy for the treatment of viral encephalitis. Such a strategy has proven effective in an animal model of herpes virus infections in the brain in which Acyclovir treatment was administered in conjunction with the use of a synthetic bradykinin analog used to temporarily permeabilize the BBB (Bidanset et al 2001). However, the data presented here, as well as other reports evaluating the connection between BBB permeability and viral encephalitis (Lustig et al 1992;Ben-Nathan et al 2000), would indicate that any therapy aimed at increasing BBB permeability would be contraindicated in BaV and SFV animal models, as well as in individuals infected with related members of the Flavivirus-and Togavirus families of viruses.…”
Section: Discussionmentioning
confidence: 99%
“…Opening the barrier by stimulating tight junctions in the BBB/BSCB, through the use of biological, chemical or physical stimuli, has been the most widely used method of drug delivery. For example, Cereport, a synthetic peptide that can disrupt tight junctions, has been widely studied for BBB permeability and therapeutic approaches 8 9 . The use of high-intensity-focused ultrasound has also been investigated to physically enhance drug delivery into the CNS for therapeutic purposes 10 .…”
mentioning
confidence: 99%